2013
DOI: 10.1590/s1519-38292013000400005
|View full text |Cite
|
Sign up to set email alerts
|

Opiniao das maes sobre a posicao do bebe dormir apos campanha nacional: estudo de base populacional no extremo sul do Brasil

Abstract: OBJETIVOS: avaliou-se o conhecimento materno sobre a posição do bebê dormir após campanha nacional. MÉTODOS: aplicou-se questionário padronizado às mães que tiveram filho em 2010 em Rio Grande, RS. RESULTADOS: dentre as 2395 mães entrevistadas, 20% referiram conforme campanha o decúbito dorsal como a melhor posição para o bebê dormir. Destas, 39% disseram ter obtido este conhecimento junto à campanha nacional. Dentre aquelas que indicaram o decúbito lateral como posição correta, 74% disseram ter aprendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
4
0
3
Order By: Relevance
“…The probability of sleeping in the supine position increased 43% and 49%, respectively, among mothers who received counselling from doctors or other health professionals 26 . However, another study showed that only 20% of mothers were aware of the correct position for sleeping and only 29% had received this information from doctors 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The probability of sleeping in the supine position increased 43% and 49%, respectively, among mothers who received counselling from doctors or other health professionals 26 . However, another study showed that only 20% of mothers were aware of the correct position for sleeping and only 29% had received this information from doctors 27 .…”
Section: Discussionmentioning
confidence: 99%
“…A probabilidade de o bebê dormir em posição supina aumentou 43% e 49% entre mães que receberam orientação por médico ou outro profissional da saúde, respectivamente 26 . Entretanto, outro estudo evidenciou que apenas 20% das mães entrevistadas sabiam a posição correta para o bebê dormir, e somente 29% delas referiram que tinham recebido esta informação de médicos 27 .…”
Section: Discussionunclassified
“…A study conducted in the State of Rio Grande do Sul in 2006 showing that only 4% of mothers reported putting their babies to sleep in the supine position and a mere 0.1% received guidance on safe sleeping positions from paediatricians 29. Another study in the same state revealed that 20% of mothers knew the safest sleeping position, with only 29% reporting having received this information from their doctor 40. A study published in 2019 showed that babies whose mothers had received counselling on safe sleeping positions from a doctor or other health professional were 43% and 49% more likely, respectively, to sleep in the supine position than those whose mothers had not received counselling 28…”
Section: Discussionmentioning
confidence: 99%
“…29 Another study in the same state revealed that 20% of mothers knew the safest sleeping position, with only 29% reporting having received this information from their doctor. 40 A study published in 2019 showed that babies whose mothers had received counselling on safe sleeping positions from a doctor or other health professional were 43% and 49% more likely, respectively, to sleep in the supine position than those whose mothers had not received counselling. 28 …”
Section: Discussionmentioning
confidence: 99%